Grid-impact factors of field-tested residential Proton Exchange Membrane Fuel Cell systems - Paulus, Nicolas; Lemort, Vincent (CLIMA 2022 conference, 2022)
Much needed energy transition currently brings focus on micro-combined heat and power (mCHP) systems for residential uses, especially on low-capacity fuel cells (about 1 kWel) because it has been reported that they allow for increased CO2 savings per kWel compared to engine-based mCHP’s [1]. One of those (already commercialized), is a Proton Exchange Membrane Fuel Cell (PEMFC) system hybridized with a conventional gas condensing boiler. It is fed by natural gas; it is designed to cover all the heat demands of residential houses as well as to participate locally in the electrical production. Thanks to high integration levels, it combines a PEMFC of nominal constant power of 0.75kWel and 1.1kWth, a 220L DHW (Domestic Hot Water) tank and a condensing gas boiler, mainly used for peak heat demands, that designed to provide up to 30.8kWth. The financial incentive representing a major factor in the investor’s decision towards such a technological change, focus will indeed be brought on supply and demand cover factors since they are directly linked to how much the citizens are individually billed and since they constitute actual and future unavoidable keys in the energy transition, as more and more intermittent renewable energies will be integrated to the energetic mix. This study is monitoring two of those installations in residential houses in Belgium, arbitrary chosen, for the whole year 2020. Sampling time of the monitoring hardware is between 2 and 5 minutes but it has been chosen to analyse the grid impacts factors according to average daily values (along with their seasonal trend and yearly figures). This paper has established yearly supply cover factors between 34 and 36%, which are believed to be higher (based upon literature) that what typical photovoltaics (PV) power plants would have allowed. It unfortunately remains lower than the 37.46% “prosumer” limit considered in the tariffication of Wallonia PV installations [2]. On the other hand, this paper has established yearly demand cover factors of 25 and 33%.